2001
DOI: 10.1300/j054v08n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Museums: An Empirical Investigation Among Museum Visitors

Abstract: This study of museum visitors was conducted in 24Historical and Museum sites in Pennsylvania. The study was designed to discover service quality, and the needs, wants, interest and satisfaction level of all visitors so that the 24 museum sites around the state of Pennsylvania can serve the public at a higher level.A self-administrated questionnaire was used to gather information. A reasonable number of visitors were selected using systematic and random selection procedures. According to this sampling method, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
1
9
0
7
Order By: Relevance
“…4 In an empirical study of service quality in museums, Yucelt identifies several dimensions that drive satisfaction with the museum experience, including the quality of offerings, amenities and convenience. 5 In a study of symphony audience segmentation, Garber et al found that, while the actual symphony performance was an important driver of satisfaction, it was '. .…”
mentioning
confidence: 99%
“…4 In an empirical study of service quality in museums, Yucelt identifies several dimensions that drive satisfaction with the museum experience, including the quality of offerings, amenities and convenience. 5 In a study of symphony audience segmentation, Garber et al found that, while the actual symphony performance was an important driver of satisfaction, it was '. .…”
mentioning
confidence: 99%
“…Schließlich hat auch die Marketingperspektive ihren Platz im Spektrum der Zugangsweisen zu Fragen des Museumspublikums (vgl. Gün-ter 1997, Schuck-Wersig & Wersig 1994, Yucelt 2000. Darüber hinaus hat sich die Publikumsforschung geöffnet für vielfältige Impulse, seien es Managementmethoden wie Benchmarking, die Freizeit-und Tourismusforschung oder die Cultural Studies.…”
Section: Ansätze Und Methoden Der Publikumsforschungunclassified
“…Davies 1994, Gerritson 1987, Jensen 1997, Lord & Lord 1988, Schuck-Wersig, Schneider & Wersig 1988, Yucelt 2000. Während vielfach Fragen zu kommunikationspolitischen Maßnahmen wie Öffentlich-keitsarbeit dominieren, widmen sich andere Studien prinzipieller dem Thema Publikumsentwicklung (vgl.…”
Section: Ausweitung Und Etablierung Der Publikumsforschungunclassified
“…Yücelt (2000) araştırmasında müze ziyaretçilerinin hizmet kalitesi algılamalarını ölçmüştür. Müze personeli ve rehberlerin nezaketi, cana yakınlığı, her an hizmete hazır olması gibi değerler yüksek çıkmıştır.…”
Section: Kuramsal çErçeveunclassified